Dra‘ Abu el-Naga, Ägypten. Möbelfunde in Dra' Abu el-Naga - Hilbig, Anja (e-Forschungsberichte des DAI, 2020)
Since 2014, a project has been undertaken to filter the fragmentarily-preserved furniture from the innumerable wooden fragments that have been recorded throughout the necropolis of Dra‘ Abu el-Naga (Western Thebes). While only the individual pieces of three completely-preserved boxes, one table and one stool were in evidence at the start of the project, a multitude of various types of furniture have been identified in the meantime. In the frame of the investigation, the varying construction and surface features of the furniture pieces have been analysed in order to obtain information on the manufacturing process and also on the possible use of the objects over a longer period of time. Furthermore, an in-depth evaluation of the finds context of the individual fragments provides insights into the association of the furniture pieces within the necropolis as a whole with the aim of clarifying the question which burial once contained which object.